Differentiation in Cognitive Abilities Beyond g: The Emergence of Domain-Specific Variance in Childhood - Bardach, Lisa; Kalinowski, Robert; Bailey, Drew H. (Psychological science, 2025)
Understanding how the structure of cognitive abilities changes depending on age and ability (age and ability differentiation) has critical implications for cognitive-ability assessments and cognitive-developmental theories. Most differentiation research has focused on general intelligence; however, we argue that the investments children make in specific domains and school-taught subjects should rather affect their domain-specific ability structures. Leveraging a representative longitudinal sample of 17,979 U.S. children who were assessed in mathematics, reading, science, working memory, and cognitive flexibility, we found that loadings on a general intelligence factor remained similar, whereas most domain-specific factor loadings increased over time. Hence, age and ability differentiation are conceptually distinct, with the former pertaining to specific abilities and the latter to general intelligence. We find some evidence that domain-specific abilities can compensate for lower general intelligence. Overall, our results encourage a nuanced understanding of children’s cognitive development.